Challenges in 2D Stellar Modeling - Lovekin, Catherine C. (Frontiers in Astronomy and Space Sciences, 2020)
Traditionally, stellar structure and evolution have been modelled with a series of concentric spherical shells. This description allows the star to be modelled in 1 dimension, greatly simplifying the calculations. However, as our understanding of stars becomes more advanced, the effects of non-symmetric effects must be included, which necessitates 2 or even 3 dimensional simulations. In this work, I discuss how 2D stellar models can help understand stars, improving our models of their pulsation frequencies, and allow us to place better constraints on their internal convection.